2021
DOI: 10.1111/ivb.12335
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction and early life stages of the poecilosclerid sponge Crella incrustans

Abstract: The majority of benthic invertebrates are characterized by complex life cycles that include one or more free-swimming larval stages

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Histological sections of S. australiensis from the severe hypoxia experiments were analyzed to calculate the percentage of the sponge body occupied by the aquiferous system (system of connected water channels inside the sponge). At T-end, two contracted sponges for each experimental chamber (n = 6 per treatment) were fixed and processed following the methods of Strano et al (2021). Three replicate sections for each sponge were then analysed under a dissecting microscope (Olympus SZ61) and photographed using a Canon EOS 70D digital camera.…”
Section: Histologymentioning
confidence: 99%
“…Histological sections of S. australiensis from the severe hypoxia experiments were analyzed to calculate the percentage of the sponge body occupied by the aquiferous system (system of connected water channels inside the sponge). At T-end, two contracted sponges for each experimental chamber (n = 6 per treatment) were fixed and processed following the methods of Strano et al (2021). Three replicate sections for each sponge were then analysed under a dissecting microscope (Olympus SZ61) and photographed using a Canon EOS 70D digital camera.…”
Section: Histologymentioning
confidence: 99%
“…Tissue regression involves an internal and external reorganization of sponge anatomy, including the reabsorption of the aquiferous system and, in some cases, reproductive structures including embryos and larvae [ 60 ]. Crella incrustans is a viviparous sponge that broods embryos and releases fully developed larvae through the canals of the aquiferous system during the Australasian summer [ 41 ]. Heatwave conditions and tissue regression did not inhibit C. incrustans from releasing larvae and we detected no significant effects of these conditions on larval release.…”
Section: Discussionmentioning
confidence: 99%
“…Heatwave conditions and tissue regression did not inhibit C. incrustans from releasing larvae and we detected no significant effects of these conditions on larval release. Previous histological observations of C. incrustans found that only 57% of sponges sampled between January and March 2020 ( n = 30) had embryos at different developmental stages [ 41 ]. This indicates that not all of the sponges we collected released larvae during experiment 1, and this probably reflects natural variability present in the source population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations